MurÄbaá¸¥a Reconstruction: Its Application in the Electronic Journal in Indonesia - Hasan, Muhammad (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2020)
This study aims to look at changes in murÄbaá¸¥a, both in terms of theory and practice in contemporary banking. Contemporary murÄbaá¸¥a practices refer to articles and research results that are circulating very dynamically and in some aspects undergo an update or modification. This research explores contemporary scientific articles on murÄbaá¸¥a circulating in cyberspace, which do not experience changes at the concept level but a change in practice. Murabaha, like special sales, often does not appear to be a murÄbaá¸¥a practice, even the terms of the sale and purchase agreement cannot be done. This study found that murÄbaá¸¥a changed in terms of contracts, pricing, and some conditions.